Answer:
4)
Step-by-step explanation:
the answer to seven less than a number is 4)
To solve this equation by elimination, what you would do is multiply one of the equations by -1, or distribute -1 to each term in the equation, any of the 2 equations. Then align the equations and add them together.
-(X + 3y = 3)
-X - 3y = -3
-X - 3y = -3
X + 6y = 3
__________
3y = 0
y = 0/3 = 0.
Now we can solve for x, by simply plugging the value of y into any of the 2 equations.
X + 6y = 3
X + 6(0) = 3
X + 0 = 3
X = 3.
The solution to your system of equations would be (3,0).
Check this by plugging in the point to the other equation and see if it is true.
X + 3y = 3
(3) + 3(0) = 3
3 + 0 = 3
3 = 3.
Thus it is the solution.
Answer:
a .8
b .03
c .125
d 125.0
Step-by-step explanation:
Answer:
55600
Step-by-step explanation:
5.56*10^4
(5x+3) is the width, its factors form is (5x+3)(3x-5)